Measuring the Digital Assets, Brand Services and Service Quality Quantitative Analysis: Evidence from China - Cui, Jun; Liu, Hongchen; Wan, Qiang (International Journal of Social Sciences and Public Administration, 2024)
This study mainly analyses over the data of 300 questionnaire surveys for China mobile, China, Unicom, and China Telcom. It uses the hypothesis testing methodology, ANOVA analysis, and multiple-linear regression testing methodology for data analysis and verification to prove the feasibility of the sample data. This study emphasizes the importance of using the established SERVQUAL model to measure the digital asserts, brand service, and quality-of-service of the mobile communications segment in China, albeit with fair variance based on expert judgments to capture specific industry aspects, as well as China’s unique digital and brand culture. Moreover, it is challenging to find evidence-backed studies focusing on quality-of-service, consumer satisfaction and consumer value, along with their impacts on the behaviour intentions of consumers in the telecommunications sector. This study emphasizes the importance of using the established SERVQUAL model to measure the quality-of-service of the mobile communications segment in China, albeit with fair variance based on expert judgments to capture specific industry aspects, as well as China’s unique culture. Meanwhile, This article uses a combination of qualitative and quantitative methods for analysis. This article mainly uses quantitative analysis methodology for sample research, it also uses SPSS and Excel software as analysis tool. The major factors of quality-of-service, consumer value, brand value, digital asserts value, and consumer happiness are initially determined using a disaggregated method to stress the consumer perceived sacrifice. Following that, the paper focuses on establishing dynamic relationships between those elements, particularly the regulating role of consumer value in the customerr relationship between higher-quality of service and some related consumer satisfaction, which is preceded by a finally examination of their effects on consumers’ behaviour and behaviour data. The paper research results are based on our structural equation models that were created using the TAM theory method - Partial Least Square approach.